Acute consumption of a branched chain amino acid and vitamin B-6 containing sports drink does not improve multiple sprint exercise performance, but increases post-exercise blood glucose - Farra, Saro D. (Frontiers in Nutrition, 2023)
Purpose The aim of this study was to investigate the ergogenicity of BioSteel High Performance Sports Drink (B-HPSD), a commercially available branched chain amino acid (BCAA) and vitamin B-6 (VitB-6) supplement, on multiple sprint exercise (MSE). Methods Eleven experienced cyclists completed two MSE trials in counterbalanced order, after ingesting either B-HPSD (2,256 mg of BCAA, 300 mcg of VitB-6) or placebo (PLA). The MSE protocol consisted of five maximal effort 1 km sprints on a cycle ergometer separated by 2 min of active recovery. Power output (PO) was continuously measured throughout the cycling protocol. Heart rate (HR) and ratings of perceived exertion (RPE) were monitored following each sprint. Capillary blood samples were collected and analyzed for lactate and glucose before and 2 min post-trial. Cognitive function was assessed before and 15 min after the exercise protocol. Results The PO maintained during each 1 km sprint decreased throughout the protocol (p < 0.05), but the change in PO was similar between conditions. Post-exercise blood glucose was elevated after consuming B-HPSD but not PLA (p < 0.05). Blood lactate (p < 0.05), HR (p < 0.05) and RPE (p < 0.05) increased throughout the trials, however no differences were observed between conditions. Cognitive performance improved after exercise (p < 0.05), but the change was similar between conditions. Conclusion These results demonstrate that acute B-HPSD consumption does not have an ergogenic effect on MSE performance. However, ingestion of B-HPSD increased post-exercise blood glucose concentration when compared to PLA.